From Pulpit to Platform: Digital Literacy and the Reconfiguration of Religious Authority among State Counselors in West Sumatra - Abdullah Khusairi; Ahmad Khoirul Fata; Abdul Ghafar Don Don (Jurnal Theologia, 2025)
This study examines the transformation of Islamic preaching from traditional spaces to digital platforms, focusing on the experiences of state religious counselors in West Sumatra. The unit of analysis is the group of penyuluh agama (religious counselors) under Indonesia's Ministry of Religious Affairs who are adapting their da'wah practices to the algorithmic dynamics of social media. The study aims to explore their level of digital literacy, the challenges they encounter in online preaching, and how these affect their religious authority in a digitally mediated society. Using a qualitative approach, data were collected through Focus Group Discussions (FGDs) involving 19 counselors across several districts, and analyzed using the Miles and Huberman interactive model. The findings reveal that most counselors possess low digital literacy and rely on informal learning, resulting in limited online engagement and visibility. Challenges include a lack of technical training, inadequate institutional support, and fear of online misinterpretation. However, participants recognize the potential of digital media to expand da'wah outreach if supported by structured literacy programs and creative content strategies. This study contributes to understanding how state religious authority is being reconfigured in the digital age and provides policy insights for strengthening digital competence within Islamic counseling institutions.